2017
DOI: 10.1016/j.yexmp.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of DNA methylation profiles between breast core biopsy and surgical excision specimens containing ductal carcinoma in situ (DCIS)

Abstract: The utility and reliability of assessing molecular biomarkers for translational applications on pre-operative core biopsy specimens assume consistency of molecular profiles with larger surgical specimens. Whether DNA methylation in ductal carcinoma in situ (DCIS), measured in core biopsy and surgical specimens are similar, remains unclear. Here, we compared genome-scale DNA methylation measured in matched core biopsy and surgical specimens from DCIS, including specific DNA methylation biomarkers of subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The molecular mechanism underlying MYC overexpression in ENKTL is interesting since, unlike B-cell lymphomas, gene rearrangements involving MYC are absent or very rare, although increased MYC copy number is present in a subset of ENKTLs. 54 In the present study, ENKTLs with high MYC expression were enriched in those with mutations in the BCOR gene, encoding the BCL6 corepressor BCOR, which have been reported in T-cell– and NK-cell–derived malignancies with varying frequencies. 12 , 13 , 15 , 16 , 17 , 18 In ENKTL, the frequency of BCOR mutations varies from 0% to 32%.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The molecular mechanism underlying MYC overexpression in ENKTL is interesting since, unlike B-cell lymphomas, gene rearrangements involving MYC are absent or very rare, although increased MYC copy number is present in a subset of ENKTLs. 54 In the present study, ENKTLs with high MYC expression were enriched in those with mutations in the BCOR gene, encoding the BCL6 corepressor BCOR, which have been reported in T-cell– and NK-cell–derived malignancies with varying frequencies. 12 , 13 , 15 , 16 , 17 , 18 In ENKTL, the frequency of BCOR mutations varies from 0% to 32%.…”
Section: Discussionsupporting
confidence: 59%
“… 53 A study by Chen and colleagues of 54 patients with ENKTL found that OS was significantly shorter in the MYC + group (defined as positivity ≥40%). 54 Although they used different cutoff values, all showed high MYC expression to be an independent prognostic factor by multivariate analyses. Our finding further confirms the utility of MYC IHC for risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the biological findings of this study, especially the downregulated immune-related pathways, need elucidation partly because acquiring SATs for expression analysis requires a biopsy. Since molecular changes such as wound healing can be detected after solidtissue biopsy, 14 future studies should consider evaluating less invasive procedures (e.g., blood sampling) that can detect bariatric surgery- associated changes with minimal bias. It will also be interesting to identify the specific cell types that contribute to such molecular changes, possibly through novel cell-type deconvolution methods, single-cell approaches, and integration of other molecular data types.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). HM450 and EPIC array DNA methylation data for selected projects comprising selected adenocarcinomas, available liver metastases and cfDNA (GSE75041, GSE113017 85 , GSE113019 85 , GSE217384 61 , GSE201241 86 , GSE49656 87 , GSE220160, GSE119526 88 , GSE149282 89 , GSE159898 90 , GSE63704 91 , GSE134217 92 , GSE207846 93 , GSE99553 94 , GSE100503 95 , GSE88883 96 , GSE212375 14 , GSE122126 12 ) were downloaded. Where available, the raw data were downloaded and used to perform quality control, normalization and calculation of the beta value with the minfi package 97 .…”
Section: Methodsmentioning
confidence: 99%